Progress in location-based services 2016 - Gartner, Georg F., 1966-; Huang, Haosheng, 1968- (Springer, 2016)
This book offers a selection of the best papers presented at the 13th International Symposium on Location Based Services (LBS 2016), which was held in Vienna (Austria) from November 14 to 16, 2016. It provides an overview of recent research in the field, including the latest advances in outdoor/indoor positioning, smart environment, spatial modeling, personalization and context awareness, cartographic communication, novel user interfaces, crowd sourcing, social media, big data analysis, usability and privacy.
Keywords: Location-based services.; elektronické knihy; electronic books